2018
DOI: 10.3389/fvets.2018.00017
|View full text |Cite
|
Sign up to set email alerts
|

Noise Sensitivities in Dogs: An Exploration of Signs in Dogs with and without Musculoskeletal Pain Using Qualitative Content Analysis

Abstract: Noise sensitivity is a common behaviour problem in dogs. In humans, there is a well-established relationship between painful conditions and the development of fear-related avoidance responses. Whilst it is likely that a relationship exists between noise sensitivity and pain in dogs, this does not appear to have been investigated. The aim of this study was to explore the signs of noise sensitivity in dogs with and without musculoskeletal pain by comparing case histories using qualitative content analysis. Data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 27 publications
1
41
0
Order By: Relevance
“…Previous studies have reported increased anxiety in aged dogs, including increased neuroticism (40), fear of handling, fear of noises (14,41,66) and human and object fear (34). Since older dogs are more likely to suffer from painful conditions (e.g., osteoarthritis) (67), when not medicated, pain can cause changes in behavior such as increased anxiety and noise sensitivity (68). Unfortunately, the DPQ does not include questions about noise fear, and so we were not able to examine its relationship with age.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported increased anxiety in aged dogs, including increased neuroticism (40), fear of handling, fear of noises (14,41,66) and human and object fear (34). Since older dogs are more likely to suffer from painful conditions (e.g., osteoarthritis) (67), when not medicated, pain can cause changes in behavior such as increased anxiety and noise sensitivity (68). Unfortunately, the DPQ does not include questions about noise fear, and so we were not able to examine its relationship with age.…”
Section: Discussionmentioning
confidence: 99%
“…It may be that animals with pain can suffer from anxiety, and that anxiety leads to a pessimistic cognitive bias that also leads to fear reactions in dogs. Although further studies are needed in order to confirm this hypothesis, one recent clinical case study [20], with a small sample size, suggests a qualitative relationship between pain and noise sensitivity. In this study, 20 dogs with noise sensitivity were divided in two groups, 10 dogs that showed noise sensitivity and pain (clinical case group), and 10 that only showed noise sensitivity (control group).…”
Section: Pain and Fearsmentioning
confidence: 99%
“…Associations between certain forms of common behavior problems in dogs (i.e., aggressive behavior, noise sensitivities) and chronic musculoskeletal pain have recently been described [1][2][3], and clearly there is a need to differentiate these pain-related conditions from ones that do not feature pain. However, pain-related effects may not manifest directly in a primary behavior complaint, but rather they may moderate a pre-existing behavioral condition or present unusual signs in association with a case.…”
Section: Introductionmentioning
confidence: 99%
“…The latter is noted by Barcelos et al [2] in relation to dogs showing aggressive behavior, with those in chronic pain tending to show aggressive behavior towards a wider range of subjects (familiar and/or unfamiliar, humans and/or dogs). Fagundes and colleagues [3], in a qualitative analysis of noise sensitive dogs with and without musculoskeletal pain, identified several factors relating to the nature of the response that might be suggestive of pain involvement. In particular, there appeared to be a greater tendency to avoid a very wide range of locations associated with the noise in these animals compared to non-pain controls.…”
mentioning
confidence: 99%